Preface: Intent, attention, interpretation - Panao, Rogelio Alicor L. (Philippine Social Sciences Review, 2016)
Attention is virtue. To the attentive, the past may present a different picture and historical narratives may lead to startling new conclusions. With the advent of new media and information technology, however, not only has attention become a scarce commodity it has also evolved into currency to buy the attention of others (Hagner, 2003). In this issue of the Philippine Social Sciences Review, five articles tackle attention and how it relates to language evolution, historical anachronism, missionary work, and legislative policymaking.